Reprodução induzida e desenvolvimento inicial do Jundiá Leiarius marmoratus (PISCES: SILURIDAE) - Mira López, Tatiana María [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Jundiá (Leiarius marmoratus) is a siluriform fish of the family Pimelodidae with reproductive migration during the rainy season, which occur in the basins of the Amazon and Orinoco rivers. It is a species of great economic value for its favorable husbandry characteristics, as little cannibalism in hatchery phase and good acceptance of dry foods in adulthood. It may be a vulnerable species due to changes in habitat because its reofilic behavior in at least one stage of its life cycle. In this context, studies that provide an appropriate captive breeding and knowledge of the biology of early development of the species, are sorely needed, aiming to produce juveniles for aquaculture or to support conservation programs their populations. The present study aims to establish a protocol for captive breeding with two hormonal substances, crude carp pituitary extract (EHC) and Ovopel ® (OVO: mGnRHa + metoclopramide), and describe the development of embryos and growth of larvae L. marmoratus. To establish the induction and reproduction protocols, males and females were selected based on observing external characteristics indicative of reproductive maturity, as bulging belly in females and emission of semen in males. Males were injected with OVO in total dosage of 2.5 mg.kg-1. In females, two inducing substances were tested: one group was injected in total dosage of 5.5 mg.kg-1 EHC and a second group was injected in total dosage of 5.5 mg.kg-1 of OVO. Females responded with oocytes elimination with 175.9 and 177.2 hours-degree for EHC and OVO at an average water temperature of 25.5 ± 8.8 ° C (p> 0,05). The diameter of ovulated oocytes was 665 ± 3.11 μm. Reproductive parameters such as the total and relative fecundity, and fertility were the same for both inducing substances (p> 0.05), with values of 612,000 and 605,400 oocytes.female-1 (fecundity), 125,800 and 132,000 oocytes.kg-1 body weight of the female (fecundity on weight) and 74.7 ...

O Jundiá Leiarius marmoratus é um peixe siluriforme da família Pimelodidae, com migração reprodutiva durante a época de chuvas e que ocorre nas bacias dos rios Amazonas e Orinoco. É uma espécie de grande valor econômico por suas características zootécnicas favoráveis, como pouco canibalismo na fase de larvicultura e boa aceitação de alimentos secos na fase adulta. Pode ser uma espécie vulnerável às alterações de hábitat em função do comportamento essencialmente reofílico em pelo menos uma fase do seu ciclo de vida. Neste contexto, estudos que possibilitem a reprodução adequada em cativeiro e o conhecimento da biologia do desenvolvimento inicial da espécie são extremamente necessários, visando produzir juvenis para a aquicultura ou para subsidiar os programas de conservação das suas populações. O presente estudo tem como objetivo estabelecer um protocolo de reprodução em cativeiro com duas substâncias hormonais, extrato bruto de hipófise de carpa (EHC) e Ovopel® (OVO: mGnRHa + metoclopramida), e descrever o desenvolvimento de embriões e o crescimento das larvas do L. marmoratus. Para o estabelecimento dos protocolos de indução à reprodução, machos e fêmeas adultos foram selecionados com base na observação de características externas indicadoras de maturidade reprodutiva, como ventre abaulado nas fêmeas e liberação de sêmen nos machos. Os machos foram injetados com OVO na dosagem total de 2,5 mg.kg-1. Nas fêmeas foram testadas duas substâncias indutoras: um grupo foi injetado com EHC na dosagem total de 5,5 mg.kg-1 e um segundo grupo foi injetado com OVO na dosagem total de 5,5 mg.kg-1. As fêmeas responderam eliminando ovócitos com 175,9 e 177,2 horas-grau para EHC e OVO, respectivamente, a uma temperatura média da água de 25,5 ± 8,8 °C (p>0.05). O diâmetro dos ovócitos ovulados foi de 665 ± 3,11 μm. Parâmetros reprodutivos tais como fecundidade total e relativa e fertilidade foram ...
Keywords: Peixe - Reprodução; Jundiá (Peixe); Bagre (Peixe); Biologia do desenvolvimento; Especies em extinção; Fishes - Reproduction